Ceramicines M–P from Chisocheton ceramicus: isolation and structure–activity relationship study - Nugroho, Alfarius Eko; Hashimoto, Akiyo; Wong, Chin-Piow; Yokoe, Hiromasa; Tsubuki, Masayoshi; Kaneda, Toshio; A. Hadi, A. Hamid; Morita, Hiroshi (Springer Verlag (Germany), 2018)
Ceramicines are a series of limonoids which were isolated from the bark of Malaysian Chisocheton ceramicus (Meliaceae) and show various biological activities. Ceramicine B, in particular, has been reported to show a strong lipid droplet accumulation (LDA) inhibitory activity on a mouse pre-adipocyte cell line (MC3T3-G2/PA6). With the purpose of discovering compounds with stronger activity than ceramicine B, we further investigated the constituents of C. ceramicus. As a result, from the bark of C. ceramicus four new ceramicines (ceramicines M–P, 1–4) were isolated, and their structures were determined on the basis of NMR and mass spectroscopic analyses in combination with NMR chemical shift calculations. LDA inhibitory activity of 1–4 was evaluated. Compounds 1–3 showed LDA inhibitory activity, and 3 showed better selectivity than ceramicine B while showing activity at the same order of magnitude as ceramicine B. Since 3, which possess a carbonyl group at C-7, showed better selectivity than 5, which possess a 7α-OH group, while showing activity at the same order of magnitude as 5, we also investigated the effect of the substituent at C-7 by synthesizing several derivatives and evaluating their LDA inhibitory activity. Accordingly, we confirmed the importance of the presence of a 7α-OH group to the LDA inhibitory activity.